PELATIHAN PENULISAN DAN PUBLIKASI ILMIAH DALAM RANGKA UPGRADING SKILL DI UNIVERSITAS PEKALONGAN - Zafrizal, Meliza (Universitas Mataram, 2024)
The minimal number of scientific publications produced by students at Pekalongan University is one of the obstacles in increasing the accreditation ranking of study programs and universities. This is due to students' lack of knowledge and ability to write scientifically and publish their writing in journal articles. Therefore, scientific writing and publication training is needed so that students receive information on how to write journal articles and publish these articles in national and international journals. The training method is carried out in three stages, namely an initial survey before the training is carried out, presentation of the training material, and a final survey as an evaluation of the training results. The results of the training showed that 82% of participants understood the systematics of writing articles for publication. In addition, 74% of training participants understand about national and international journals based on their accreditation rankings. Apart from that, 70% of participants also understood the journal submission process via the open journal system (OJS). Scientific writing and publication training is very necessary for students and is expected to increase the quantity and quality of student scientific publications at Pekalongan University.